Identification of linderalactone as a natural inhibitor of SHP2 to ameliorate CCl4-induced liver fibrosis - Zhang, Yi; Cai, Binhao; Li, Yingying; Xu, Ying; Wang, Yuhan; Zheng, Lulu; Zheng, Xiaochun; Yin, Lina; Chen, Gaozhi; Wang, Yunxiang; Liang, Guang; Chen, Lingfeng (Frontiers in Pharmacology, 2023)
Liver fibrosis is characterised by the activation of hepatic stellate cells (HSCs) and matrix deposition. Accumulating evidence has revealed that the oncogenic protein tyrosine phosphatase Src homology 2 domain-containing phosphatase 2 (SHP2) acts as a therapeutic target of fibrosis. Although several SHP2 inhibitors have reached early clinical trials, there are currently no FDA-approved drugs that target SHP2. In this study, we aimed to identify novel SHP2 inhibitors from an in-house natural product library to treat liver fibrosis. Out of the screened 800 compounds, a furanogermacrane sesquiterpene, linderalactone (LIN), significantly inhibited SHP2 dephosphorylation activity in vitro. Cross-validated enzymatic assays, bio-layer interferometry (BLI) assays, and site-directed mutagenesis were used to confirm that LIN directly binds to the catalytic PTP domain of SHP2. In vivo administration of LIN significantly ameliorated carbon tetrachloride (CCl4)-induced HSC activation and liver fibrosis by inhibiting the TGFβ/Smad3 pathway. Thus, LIN or its derivatives could be considered potential therapeutic agents against SHP2-related diseases, such as liver fibrosis or NASH.